Post-polymerization functionalization of poly(ethylene oxide)–poly(β-6-heptenolactone) diblock copolymers to tune properties and self-assembly. Issue 3 (2nd December 2016) - Raycraft, Brooke M.; MacDonald, Jarret P.; McIntosh, James T.; Shaver, Michael P.; Gillies, Elizabeth R.
Abstract : Copolymers were synthesized and functionalized with a variety of moieties to tune self-assembly and install drugs or fluorescent dyes. Abstract : Polyester-based amphiphilic block copolymers and their nanoassemblies are of significant interest for a wide range of applications due to the degradability of the polyester block. However, the commonly used polyesters lack functional groups on their backbones, limiting the possibilities to chemically modify these polymers. Described here are new poly(ethylene oxide) (PEO)–poly(β-6-heptenolactone) (PHEL) block copolymers having pendant alkenes at each repeat unit on the PHEL block. First, the self-assembly of these block copolymers in aqueous solution was studied and it was found that they formed solid nanoparticles and vesicles depending on the relative block lengths. Next the alkene moieties of the block copolymer were modified with either hydrophilic or hydrophobic pendant groups using thiol–ene reactions, allowing the hydrophilic mass fractions and consequently the self-assembled morphologies to be tuned, accessing both smaller nanoparticles and cylindrical assemblies. It was also demonstrated that the anti-cancer drug paclitaxel or a fluorescent rhodamine dye could be easily conjugated to the block copolymers and the self-assembly of these conjugates was explored. Overall, the results of this study demonstrate that PEO-PHEL block copolymers can serve as versatile backbones for the preparation of functional, polyester-based materials.